Additional Evidence against Shared Environmental Contributions to Attention-Deficit/Hyperactivity Problems - Burt, S. Alexandra (2012)
A recent meta-analysis (Burt, 2009) indicated that shared environmental influences (C) do not contribute to Attention-Deficit/Hyperactivity Disorder (ADHD). Unfortunately, the meta-analysis relied almost exclusively on classical twin studies. Although useful in many ways, some of the assumptions of the classical twin model (e.g., dominant genetic and shared environmental influences do not simultaneously influence the phenotype) can artifactually decrease estimates of C. There is thus a need to confirm that dominant genetic influences are not suppressing estimates of C on ADHD. The current study sought to do just this via the use of a nuclear twin family model, which allows researchers to simultaneously model and estimate dominant genetic and shared environmental influences. We examined two independent samples of child twins: 312 pairs from the Michigan State University Twin Registry (MSUTR) and 854 pairs from the PrEschool Twin Study in Sweden (PETSS). Shared environmental influences were found to be statistically indistinguishable from zero and accounted for less than 5% of the variance. We conclude that the presence of dominant genetic influences does not account for the absence of C on ADHD.